2010
DOI: 10.1186/1471-2407-10-617
|View full text |Cite
|
Sign up to set email alerts
|

TFPI-2 is a putative tumor suppressor gene frequently inactivated by promoter hypermethylation in nasopharyngeal carcinoma

Abstract: BackgroundEpigenetic silencing of tumor suppressor genes play important roles in NPC tumorgenesis. Tissue factor pathway inhibitor-2 (TFPI-2), is a protease inhibitor. Recently, TFPI-2 was suggested to be a tumor suppressor gene involved in tumorigenesis and metastasis in some cancers. In this study, we investigated whether TFPI-2 was inactivated epigenetically in nasopharyngeal carcinoma (NPC).MethodsTranscriptional expression levels of TFPI-2 was evaluated by RT-PCR. Methylation status were investigated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…frequently methylated in various other cancers as well as in lung cancer (Glöckner et al, 2009;Takadaa et al, 2010;Wang et al, 2010). Silencing of the TFPI-2 gene by hypermethylation might contribute to tumor progression in NSCLC (Rollin et al, 2005).…”
Section: Deoxycytidine Effects On Proliferation Of Nsclc A549 Cells Amentioning
confidence: 99%
“…frequently methylated in various other cancers as well as in lung cancer (Glöckner et al, 2009;Takadaa et al, 2010;Wang et al, 2010). Silencing of the TFPI-2 gene by hypermethylation might contribute to tumor progression in NSCLC (Rollin et al, 2005).…”
Section: Deoxycytidine Effects On Proliferation Of Nsclc A549 Cells Amentioning
confidence: 99%
“…Increased SER-PINE1 expression reduced migration by normal prostate cells [89]. Consistent with HGF suppression of TFPI, decreased TFPI expression has been correlated with increased cell motility, invasion and tumor metastasis in breast and pancreatic cancers, glioblastoma, melanoma and nasopharyngeal carcinoma [90][91][92][93][94]. Tissue factor pathway inhibitor (TFPI) also interferes with endothelial cell migration by inhibiting the Erk pathway and focal adhesion proteins [95].…”
Section: Metabolism and Ion Transport (Asns And Scnn1g)mentioning
confidence: 83%
“…TFPI-2 is a candidate TSG with important roles in carcinogenesis and metastasis in human cancers. Transcriptional silencing by promoter hypermethylation of TFPI-2 has been observed in some human cancers including NPC Wang et al 2010). Using methylation-specific PCR and bisulfate genomic sequencing, Wang et al (2010) found that TFPI-2 was aberrantly methylated in 88.6 % (62/70) of NPC primary tumors, but not in normal nasopharyngeal epithelia.…”
Section: Tissue Inhibitor Of Metalloproteinase-3 (Timp-3) Genementioning
confidence: 98%
“…Transcriptional silencing by promoter hypermethylation of TFPI-2 has been observed in some human cancers including NPC Wang et al 2010). Using methylation-specific PCR and bisulfate genomic sequencing, Wang et al (2010) found that TFPI-2 was aberrantly methylated in 88.6 % (62/70) of NPC primary tumors, but not in normal nasopharyngeal epithelia. The authors suggested that epigenetic inactivation of TFPI-2 by promoter hypermethylation is common and can be a specific marker for the diagnosis of NPC.…”
Section: Tissue Inhibitor Of Metalloproteinase-3 (Timp-3) Genementioning
confidence: 98%